Delivering Quality Health Services : A Global Imperative for Universal Health Coverage - World Health Organization; World Bank Group; OECD (Geneva: World Health Organization, 2018)
This document Delivering quality health services : a global imperative for universal health coverage describes the essential role of quality in the delivery of health care services. As nations commit to achieving universal health coverage by 2030, there is a growing acknowledgement that optimal health care cannot be delivered by simply ensuring coexistence of infrastructure, medical supplies and health care providers. Improvement in health care delivery requires a deliberate focus on quality of health services, which involves providing effective, safe, people-centered care that is timely, equitable, integrated and efficient. Quality of care is the degree to which health services for individuals and populations increase the likelihood of desired health outcomes and are consistent with current professional knowledge.